Analisis Sistem Informasi Manajemen Keuangan di UMKM - Nurul Huda; Ratih Kusumastuti; Achmad Hizazi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Digital transformation in the field of information technology requires Micro, Small, and Medium Enterprises (MSMEs) to improve the quality of financial management to be able to compete sustainably. One effort that can be done is through the implementation of the Financial Management Information System (MISK). This study aims to analyze the implementation of MISK in MSMEs, examine the benefits obtained, and identify obstacles faced in the implementation process. The research method used is a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The object of the study is the culinary MSME